Ferroptosis in pulmonary fibrosis: an emerging therapeutic target - Wang, Chunyan; Hua, Shucheng; Song, Lei (Frontiers in Physiology, 2023)
In recent years, the role of ferroptosis in pulmonary fibrosis has garnered increasing interest as a potential therapeutic target. Pulmonary fibrosis is a pathological process characterized by the accumulation of extracellular matrix in affected lung tissues, and currently, there are no effective therapies for preventing or reversing the fibrotic lesions. Ferroptosis is a form of programmed cell death that is regulated by a network of enzymes and signaling pathways. Dysregulation of ferroptosis has been implicated in several diseases, including pulmonary fibrosis. The accumulation of lipid peroxides in the course of ferroptosis causes damage to cell membranes and other cellular components, leading ultimately to cell death. Relevant targets for therapeutic intervention in ferroptosis include key enzymes, such as glutathione peroxidase 4, transcription factors like nuclear factor erythroid 2-related factor 2, and iron chelation. This review provides an overview of the emerging role of ferroptosis in pulmonary fibrosis and highlights potential therapeutic targets in this pathway. Further research is needed to develop safe and effective approaches targeting ferroptosis in treatment of pulmonary fibrosis.